2022
DOI: 10.3390/microorganisms10050972
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen- and Type-Specific Changes in Invasive Bacterial Disease Epidemiology during the First Year of the COVID-19 Pandemic in The Netherlands

Abstract: COVID-19 control measures have resulted in a decline in invasive bacterial disease caused by Neisseria meningitidis (IMD), Streptococcus pneumoniae (IPD), and Haemophilus influenzae (Hi-D). These species comprise different serogroups and serotypes that impact transmissibility and virulence. We evaluated type- and pathogen-specific changes in invasive bacterial disease epidemiology in the Netherlands during the first year of the SARS-CoV-2 pandemic. Cases were based on nationwide surveillance for five bacterial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
3
10
0
7
Order By: Relevance
“…We witnessed a decrease in both community- and hospital-acquired bloodstream infections due to S. pneumoniae and S. pyogenes concomitantly to the large implementation of preventive measures to curb the COVID-19 pandemic. These findings are in line with several reports based on either the whole population with data issued from nationwide surveillance systems 7 , 8 , or on inpatients such as the pediatric population 9 , 10 . On the opposite, one study reported an increase of such infections during intervals when COVID-19 incidence slowed down, that is to date not clearly explained 11 .…”
Section: Discussionsupporting
confidence: 92%
“…We witnessed a decrease in both community- and hospital-acquired bloodstream infections due to S. pneumoniae and S. pyogenes concomitantly to the large implementation of preventive measures to curb the COVID-19 pandemic. These findings are in line with several reports based on either the whole population with data issued from nationwide surveillance systems 7 , 8 , or on inpatients such as the pediatric population 9 , 10 . On the opposite, one study reported an increase of such infections during intervals when COVID-19 incidence slowed down, that is to date not clearly explained 11 .…”
Section: Discussionsupporting
confidence: 92%
“…Daten aus den Niederlanden bestätigen die Entwicklung in Deutschland und zeigen für das Jahr 2020 verglichen mit den Vorjahren ebenfalls eine deutliche Reduktion bakterieller Meningitiden hervorgerufen durch Pneumokokken [ 29 ]. Studien zu Kindern zeigten keine Abnahme bakterieller Meningitiden einschließlich der durch Pneumokokken, was gut mit dem abweichenden Pathomechanismus in dieser Altersgruppe zu erklären ist: Bei Kindern liegt einer bakteriellen Meningitis häufiger als bei Erwachsenen eine hämatogene Erregeraussaat zugrunde; eine fortgeleitete parameningeale Infektion wird deutlich seltener als Ursache einer Meningitis beobachtet [ 7 , 21 , 34 ].…”
Section: Pneumokokkenmeningitisunclassified
“…Andere Studien zur Meningokokken-Surveillance zeigen ebenfalls eine Abnahme invasiver Meningokokkenisolate während der Pandemie in zahlreichen Ländern [ 3 , 15 , 29 ]. Für die Niederlande liegen zudem Analysen hinsichtlich Serogruppenunterschieden vor, die für die Serogruppe B einen Rückgang um 61 % und für die Serogruppen W und Y um mehr als 90 % beschreiben [ 29 ].…”
Section: Invasive Meningokokkenerkrankungen Und Meningokokkenmeningitisunclassified
See 2 more Smart Citations